Influence of lateral ambient wind speed on fire smoke behavior in tunnel with unpowered ventilation caps shaft - Weikang Liang; Yuan Wang; Zhonghao Wen; Min Hao; Ru Zhou; Juncheng Jiang (Case Studies in Thermal Engineering)
As the use of unpowered ventilation caps continues to grow, it has the potential to be used in vertical shaft natural ventilation tunnel. However, smoke control mechanism of tunnel fire with the influence of unpowered ventilation caps need further study. This study explores how lateral ambient wind speed affects the behavior of smoke during tunnel fires with unpowered ventilation caps shaft. A 1:15 scale model tunnel with a vertical shaft is used to analyze lateral and longitudinal wind effects. And, the difference of smoke behavior in tunnel with or without unpowered ventilation caps shaft is compared. Unpowered ventilation caps reduce the average maximum ceiling temperature elevation by 10 % near the shaft compared to shafts without them. As lateral ambient wind speed increases, the maximum temperature elevation decreases gradually. Additionally, unpowered ventilation caps improve smoke exhaust efficiency, doubling the mass flow rate, which further increases with higher lateral wind speeds. A model is developed to predict the relationship between lateral wind speed and smoke exhaust efficiency for shafts with unpowered ventilation caps. The results can provide valuable insights for fire safety design in naturally ventilated tunnels and for evaluating the potential use of unpowered ventilation caps.